Corrosion behavior of aluminum-carbon fiber/epoxy sandwich composite exposed on NaCl solution - Jáquez Muñoz, Jesús Manuel; Castrejón, A, N.; Lira Martínez, Manuel Alejandro; Maldonado Bandala, Erick; Cabral Miramontes, José Ángel; Lara Banda, María del Refugio; Estupiñan López, Francisco Humberto; Nieves Mendoza, Demetrio; Gaona Tiburcio, Citlalli; Almeraya Calderón, Facundo (Frontiers Media, 2023)
For years, the aeronautical industry has employed different types of materials to satisfy its high-performance requirements. Fiber-metal laminates are used due to their combination of lighter weight and the high mechanical properties of reinforced metal and carbon. We therefore made two different composites of laminate-metal and laminate-metal-laminate of carbon fiber-reinforced polymer and aluminum with an ALCLAD layer. The samples were characterized by salt fog (0, 48, and 96 h) at 5 wt% NaCl and electrochemical impedance spectroscopy (EIS) with an electrolyte of 3.5 wt% NaCl. All samples were studied by electron scanning microscopy (SEM). The results demonstrated that the samples of laminate-metal-laminate presented an adsorption process after 0 and 48 h of salt fog exposition; meanwhile, the samples of laminate-metal showed a capacitive behavior for all the samples; however, corrosion resistance decreased when the salt fog exposition time increased.